Birds of a feather locate together? Foursquare checkins and personality homophily. (May 2016) - Noë, Nyala; Whitaker, Roger M.; Chorley, Martin J.; Pollet, Thomas V.
Abstract: In this paper we consider whether people with similar personality traits have a preference for common locations. Due to the difficulty in tracking and categorising the places that individuals choose to visit, this is largely unexplored. However, the recent popularity of location-based social networks (LBSNs) provides a means to gain new insight into this question through checkins - records that are made by LBSN users of their presence at specific street level locations. A web-based participatory survey was used to collect the personality traits and checkin behaviour of 174 anonymous users, who, through their common check-ins, formed a network with 5373 edges and an approximate edge density of 35%. We assess the degree of overlap in personality traits for users visiting common locations, as detected by user checkins. We find that people with similar high levels of conscientiousness, openness or agreeableness tended to have checked-in locations in common. The findings for extraverts were unexpected in that they did not provide evidence of individuals assorting at the same locations, contrary to predictions. Individuals high in neuroticism were in line with expectations, they did not tend to have locations in common. Unanticipated results concerning disagreeableness are of particular interest and suggest that different venue types and distinctive characteristics may act as attractors for people with particularly selective tendencies. These findings have important implications for decision-making and location. Highlights: We assess spatial homophily between users of the Foursquare social network. Users show stronger homophilic tendency when they are more open and conscientious. Disagreeable users were homophilous at a higher number of common venues visited. Contrary to expectations, extroverts had no such tendency. Neurotic users' tendency to co-locate was even less than expected by chance.